2014
DOI: 10.7314/apjcp.2014.15.14.5583
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Enhances Helicobacter pylori Induced Cell Apoptosis in Human Gastric Cancer Epithelial Cells

Abstract: Helicobacter pylori (H. pylori) infection induces apoptosis in gastric epithelial cells, and this occurrence may link to gastric carcinogenesis. However, the regulatory mechanism of H. pylori-induced apoptosis is not clear. MicroRNA-146a has been implicated as a key regulator of the immune system. This report describes our discovery of molecular mechanisms of microRNA-146a regulation of apoptosis in human gastric cancer cells. We found that overexpression of microRNA-146a by transfecting microRNA-146a mimics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…An Annexin V-Fluos staining kit (Roche-Boehringer) was used to detect early stages of apoptosis according with previous report (9). The cells were washed with phosphate-buffered saline (PBS) and stained according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An Annexin V-Fluos staining kit (Roche-Boehringer) was used to detect early stages of apoptosis according with previous report (9). The cells were washed with phosphate-buffered saline (PBS) and stained according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al (9) showed that miR-146a enhances Helicobacter pylori-induced cell apoptosis in human gastric cancer epithelial cells by targeting COX-2. Hao et al (22) demonstrated that enforced expression of miR-101 inhibits prostate cancer cell growth by modulating the COX-2 pathway.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…development, cell proliferation, cell cycle, apoptosis, migration, and differentiation (Yin et al, 2012;Chen et al, 2013;Montalban et al, 2014;Wu et al, 2014a;2014b;Zha et al, 2014;Zhong et al, 2014). They have also gained importance as they carry information about the pathophysiological nature of a disease, and thus can serve as ideal predictive biomarkers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wu et al (2014), miR-146a density was correlated with GC. Specifically, miR-146a density was positively associated with apoptosis rates in H. pylori-positive gastric tissues, which might provide a link to the gastric carcinogenesis process.…”
Section: Discussionmentioning
confidence: 99%